Strengthening the Competence of Religious Instructors Services Based on Tolerance in Multicultural Communities - Umar, Nasaruddin; Saihu, Made (Technium Social Sciences Journal, 2022)
This study aims to determine the affirmation of tolerance in a plural society through the competence of religious instructors in serving the people. The result of this research is that the competence of religious instructors in serving the people towards a tolerant religious life already has the correct perception and understanding of religious teachings and norms in building insight into plurality and multi-ethnicity. Along the way, the religions that emerged in a multicultural society were then understood by the people. Among them, there are those who understand it rationally an sich and some who understand it irrationally or mystically. Tolerance is needed to create balance and social cohesion in a multicultural society. To create a proportional attitude of religious tolerance in a multicultural society, it is necessary to cultivate an epoché attitude in serving the people.